Collection and Identification of Ethnobotanical plants used for the Treatment of Diabetes in Kakching District, Manipur, India - Khan, M. R.; Devi, L. Sarnabati; Singh, Khulem Nepoleon; Sharma, L. D. (Indian Forester, 2025)
The present work was done from May 2022 to April 2023, at the institutional Biotech-Hub, Pravabati, Mayang Imphal. It deals with collecting information about the medicinal plant species used for the treatment of diabetes by traditional healers or practitioners in the peripheral areas of four assembly constituencies of Kakching district in Manipur, as well as the identification and documentation of these species. Information about plants was collected from local herbal practitioners, elderly individuals, knowledgeable individuals, patients, and traditional healers through formal and informal conversations, interviews, and discussions. During the course of exploration, 41 medicinal plant species belonging to 37 genera and 32 families were identified and documented to have antidiabetic properties. It was observed that among all the parts, leaves were mostly used, followed by fruits. From the current findings, it was concluded that medicinal plants have the potential to replace synthetic drugs, which were restricted due to their effects.